Speltas the Promising Grain Crop of the Ukrainian Organic Production - Yudicheva, О. P.; Samoylenko, А. А.; Prodchenko, O. L. (ОНПУ, 2019)
Spelt is an extremely valuable cereal crop distinguished by the improved consumer properties as compared to wheat. Its cultivation takes place mainly in organic farms, which provides additional quality and safety of raw materials. Ukrainian enterprises produce groats, flour, pasta from spelt, which expand the grain crops’ range of cereal products and advertise this type of product to consumers. Taking into account the popularity of spelt in the countries of Western Europe, as well as the pricing policy existing in Ukraine and abroad, domestic production of spelt products is promising.
Keywords: protein; gluten; organic production; spelt